2007
DOI: 10.1128/jcm.00900-07
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Indian Equine Rotaviruses: Identification of Genotype G10,P6[1] and G1 Strains and a New VP7 Genotype (G16) Strain in Specimens from Diarrheic Foals in India

Abstract: Volume 45, no. 3,. Recently, a mistake in comparative sequence analysis in our paper was recognized. One of the authors had unknowingly used accession number Q65669, which pertains to the bovine G8 genotype NCDV-cody strain, thinking that the number represented the G6 genotype NCDV strain, and concluded on that basis that the equine strain Erv99 represented a new genotype. Sequence analysis using the NCDV sequence revealed Erv99 to be highly related to the G6 genotype. Incorporation of this correction in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The VP7 genes of strains MS2014‐0134 and DBM2016‐096 exhibited the highest nucleotide identity (99.0%‐100%) (data not shown) with Spanish equine‐like G3P[8] strain SS98244047 . The VP7 genes of the two Thai strains formed a G3 lineage‐1 with those of equine‐like G3P[8] strains from Australia and Thailand in 2013, Spain and Hungary in 2015, and Brazil, Indonesia, and Japan in 2016, as well as Japanese equine‐like G3P[4] human strains S13‐30 and S13‐45 in a common branch with equine strain Erv105 from India within animal‐like G3 lineage‐1 (Figure A). The other 96 Thai G3P[8] strains having a short RNA pattern were all demonstrated to be equine‐like G3P[8] strains (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The VP7 genes of strains MS2014‐0134 and DBM2016‐096 exhibited the highest nucleotide identity (99.0%‐100%) (data not shown) with Spanish equine‐like G3P[8] strain SS98244047 . The VP7 genes of the two Thai strains formed a G3 lineage‐1 with those of equine‐like G3P[8] strains from Australia and Thailand in 2013, Spain and Hungary in 2015, and Brazil, Indonesia, and Japan in 2016, as well as Japanese equine‐like G3P[4] human strains S13‐30 and S13‐45 in a common branch with equine strain Erv105 from India within animal‐like G3 lineage‐1 (Figure A). The other 96 Thai G3P[8] strains having a short RNA pattern were all demonstrated to be equine‐like G3P[8] strains (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, there is a serotype-based classification scheme for rotaviruses based on outer capsid proteins VP7 (designated as 'G' as it is glycoprotein) and VP4 (designated as 'P', being a protease sensitive protein) (Steele et al 2004;Desselberger et al 2005). Based on this, rotaviruses affecting domestic animals have been reported to belong to 16 G types and 27 P types (Rao et al 2000;Steele et al 2004;Desselberger et al 2005;Khamrin et al 2007;Gulati et al 2007;Martella et al 2007b). Further, Fukai et al (2007) have demonstrated that there exist group A BRV having novel G and P type specificity, which has not yet been reported among group A rotaviruses.…”
Section: The Etiological Agentmentioning
confidence: 99%
“…Majority of the strains belong to G3 or G14 with a P[12] serotype (Tsunemitsu et al 2001;Fukai et al 2006). Recently, Gulati et al (2007) have reported a G16 serotype among equine group A rotavirus.…”
Section: Disease In Other Domestic Animalsmentioning
confidence: 99%
“…1). In both NSP4 and VP7, the goat rotavirus segregated with the ovine strain RVA/Sheep-tc/ESP/OVR762/2002/G8P [14] in the E2 and G8 genotype, respectively (Fig. 1).…”
mentioning
confidence: 94%
“…Based on sequence analysis, a Korean caprine strain has been characterized as G3P [3] and E3 NSP4 genotype, and it is believed to be derived from multiple reassortment events with other animal viruses [19]. A South African rotavirus strain, Cap455, was characterised as G6P [14] (GenBank accession numbers AY128708 and AY128709 for the VP7 and VP4, respectively), a VP7/VP4 combination found sporadically in some human and animal rotaviruses [23]. Full-length genome analysis of the G6P [1] strain GO34 isolated in Bangladesh has revealed a mosaic genome composition suggestive of multiple reassortment events with ruminant and human viruses [9].…”
mentioning
confidence: 99%